METHODS OF DEVELOPING LOGICAL THINKING IN MATHEMATICS LESSONS IN PRIMARY GRADES (International journal of artificial intelligence, 2025)
This article analyzes methods for developing logical thinking in mathematics lessons in primary grades. It emphasizes the importance of using innovative methods to cultivate students' logical reasoning skills, enhance their problem-solving abilities, and foster independent thinking. The use of logical problems, interactive games, and modern pedagogical technologies in mathematics lessons can significantly boost students’ interest and achievement.